Synopsis of Braunilla Wasbauer et Kimsey, 2019 (Hymenoptera, Pompilidae): description of a new species and updated keys - Simões, Antônio Moraes; Waichert, Cecilia (Zootaxa, 2026)
Braunilla Wasbauer et Kimsey is a small Neotropical genus comprised of 12 species distributed from Argentina to Mexico. The genus has received few taxonomic studies since its first description in 1927, other than nomenclatural preposition: Braunilla (=Balboana) was proposed by Wasbauer & Kimsey to replace the homonym Balboana. Herein, we catalog all the species classified as Braunilla, describe a new species, Braunilla dasilvae Simões et Waichert, sp. nov. (Brazil: Bahia), provide diagnoses, and an identification key to the species of the genus. We discuss the status of Braunilla chacoensis and Braunilla fraterna, which were missing in the most recent studies regarding the taxon. New synonymy is proposed for Braunilla auripennis (Fabricius, 1804) (=Pompilus chacoensis Shulz, 1906, syn. nov.); and Braunilla nigrina (Banks, 1946) (=Balboana nayaritama Evans, 1966, syn. nov.). Braunilla is now known for 11 species. This study represents an update to the taxonomy of an understudied genus, providing basis for future studies within the family, and an advance in the study of the Neotropical fauna.